Edukasi Penerapan Simrs Rekam Medis Elektronik Di Instalasi Farmasi Rumah Sakit Umum Kabupaten Kediri: Education on the Implementation of Simrs Electronic Medical Records in the Kediri Regency General Hospital Pharmacy Installation - Puspita, Mariana; Rosiyawati Maruapey, Erna; Wira Qalbi, Fitdiar; Wardani, Ratna (Chakra Brahmanda Lentera Institute, 2024)
At this time, world technology is entering the era of the industrial revolution 4.0, this has an impact on the development of the health world, namely Hospital information technology regarding Medical Records. Hospitals are obliged to improve the quality of health services by taking advantage of technological developments so that they can compete well with other health service institutions. SIMRS is useful in improving hospital performance on the speed of decision-making in developing strategies. The purpose of this study in general is to analyze the factors that cause the non-optimal use of Electronic Medical Records in RSKK Pharmaceutical Installations to support services and find the right strategy in an effort to overcome this. The methods used are the fishbone diagram method, the Urgency, Seriousness, Growth (Ultrasound) method, and analyzed with Strength, Weakness, Opportunity, Threat (SWOT). . Based on the results of the assessment, a formulation of related problems was obtained regarding the solution, strategy of the EMR implementation system in RSKK pharmaceutical installations. From the results of the interview with the current RSKK Pharmaceutical Installation, one of the problems related to SIMRS is that there is still a need to improve the menus in the application to support the performance of the pharmaceutical installation and the adjustment and transfer of data from the old application used to the new application. The results of this literature study were carried out by a quantitative method, by providing questionnaires and socialization related to the SOP SIMRS EMR implementation system to pharmaceutical installation officers. The conclusion of this literature study is that human resources (HR) and organizational factors play an important role in the success of technology acceptance, SIMRS is an optimal technology development innovation for services. With this, the researcher conducts socialization in health services, especially in pharmaceutical installations in making SOPs and SIMRS process flows in the implementation of ERM in the Pharmacy Unit.